Fresh, Mechanical, and Microstructural Properties Investigation on the Combined Effect of Biomedical Waste Incinerator Ash and Bagasse Ash for High-Strength Concrete - Menker Girma; Belachew Asteray (Advances in Materials Science and Engineering)
The combination effect of supplementary cementitious materials in the production of high-strength concrete production is an effective way to reduce the amount of cement required while contributing to environmental sustainability and cost. This study aims to assess the microstructural investigation on the combined effect of biomedical waste incinerator ash (BWIA) and bagasse ash (BA) as a partial replacement of cement in high-strength concrete production. The cement was partially replaced with BA (0%, 2.5%, 5%, and 7.5%) and BWIA (0%, 2.5%, 5%, and 7.5%). The mix design was done as per the ACI 211-4R-93 mix design standard. Slump, slump flowability, density, and compaction factor tests were conducted for freshly mixed concrete. Mechanical properties of the hardened concrete from four different mixes were also determined for the 7- and 28-day cured specimens. The microstructural properties of the hardened concrete for all mixes were also investigated using scanning electron microscopy (SEM) and X-ray diffraction (XRD) tests. Based on the experimental results, the compressive strength of high-strength concrete at every 2.5% BA and 2.5% BWIA replacement of cement in the concrete mix at 7 days of curing was slightly decreased, while at 28 days of curing, the compressive strength of the control mix (51.8 MPa) decreased as compared to the mix codes' compressive strength of the BWIA and BA5 and BWIA and BA10 mix codes, at 54.8 MPa and 52.5 MPa, respectively. The SEM micrographs showed that the partial replacement of cement by the BWIA and BA leads to a decrease in the pore proportion in the enlarged interfacial transition zone (ITZ), reduced CH crystals, and a denser C–S–H gel as compared to the control specimen. The XRD pattern showed the existence of portlandite, ettringite, okenite, quartz, and calcite in the cement and aggregate phases. As a result, the usage of BWIA and BA has a significant impact on the properties of high-strength concrete in fresh, hardened, and microstructure high-strength concrete.